The Influence of Learning Quality and School Infrastructure on Student Motivation in Automotive Engineering - Arfani, Insan; Nurdin, Diding; Prihatin, Eka (Universitas Negeri Semarang, 2024)
The components of learning quality and infrastructure play a fundamental role in maintaining and forming student learning motivation. This research seeks to analyze the influence of learning quality and infrastructure on student learning motivation. This research uses a quantitative research approach with descriptive correlation methods. The data used in the research is primary data obtained from the results of distributing questionnaires to research subjects, namely 100 students and teachers at SMK Negeri 1 Cilengkrang, Bandung Regency. The results of this research indicate that the quality of learning is in the adequate category, in the context of learning quality it indicates that the quality of learning is at an adequate level, but still has several weaknesses or areas of improvement that need attention, such as ownership of learning media because not all students have it. Furthermore, the infrastructure is known to be in a bad category. The bad category in the context of facilities and infrastructure indicates that the condition or quality of the facilities and infrastructure is below the standards expected to carry out certain functions or activities. Based on the results obtained, it can be understood that the quality of learning and infrastructure play an important role in motivating student learning.